Hermetia illucens Fermented with Lactobacillus plantarum KCCM12757P Alleviates Dextran Sodium Sulfate-Induced Colitis in Mice - Seok Jun Son; Ah-Ram Han; Mi Jeong Sung; Sun Mee Hong; Sang-Hee Lee (MDPI AG, 2023)
Inflammatory bowel disease (IBD) can severely affect humans and animals and is difficult to treat. Black soldier fly (Hermetia illucens; Hi) larvae (BSFL) are a sustainable source of protein. However, no studies exist on the antioxidant and anti-inflammatory functions of BSFL or fermented BSFL with respect to IBD. In this study, riboflavin-producing Lactobacillus plantarum KCCM12757P was isolated from a fish farm tank, and in conjunction with hot water-extracted Hi (HeHi) (termed HeHi_Lp), was used to determine optimal fermentation conditions to increase vitamin B2 concentration. This in vivo study investigated the therapeutic effects and mechanistic role of HeHi_Lp in chronic colitis-induced murine models. Histological changes, inflammatory cytokine levels, and intestinal barrier function were explored. Gut microbial communities and gene expression in the nuclear factor (NF)-κB signaling pathway were also studied. HeHi_Lp remarkably reduced the disease activity index, inflammatory cytokine (inducible nitric oxide synthase, cyclooxygenase 2, tumor necrosis factor α, interleukin (IL-6 and IL-1β) levels, and increased body weight and colon length. HeHi_Lp administration significantly raised zonula occludens 1, occludin and claudin 1 and improved the composition of the gut microbiota and beneficial intestinal bacteria. These results suggest that HeHi_Lp can be used as a dietary supplement in pet food to alleviate colitis.